Platelet-to-lymphocyte ratio at 24h after thrombolysis is a prognostic marker in acute ischemic stroke patients - Sun, Ying-Ying; Wang, Mei-Qi; Wang, Yan; Sun, Xin; Qu, Yang; Zhu, Hong-Jing; Wang, Si-Ji; Yan, Xiu-Li; Jin, Hang; Zhang, Peng; Yang, Yi; Guo, Zhen-Ni (Frontiers in Immunology, 2022)
Background: The changes in the platelet-to-lymphocyte ratio (PLR) before and after recombinant tissue plasminogen activator (rtPA) treatment and the time point at which the PLR is a potentially valuable prognostic predictor in patients with ischemic stroke remain largely unknown. Therefore, the purpose of this study was to explore the characteristics of the PLR and evaluate their effects on clinical outcomes before and 24 h after rtPA treatment. Methods: This study included 741 consecutive patients with acute ischemic stroke who underwent intravenous thrombolysis with rtPA. We collected data on demographics, vascular risk factors, medication history, and other clinical information pertaining to all patients. Specifically, blood samples for PLR measurement were collected on admission and 24 h after stroke. The outcome was assessed by using the Modified Rankin Scale (mRS) at 3 months and whether death occurred within 3 months or not. Univariate and multivariate logistic regression analysis was used to assess the association of the PLR with the risks of poor outcome (mRS>2) and death. An individualized prediction model was established to predict poor outcome. Results: Of the 741 patients, 255 (34.4%) had poor outcome, and 43 (5.8%) died. The PLR significantly increased 24 h after rtPA in patients with poor outcome and death. Logistic analysis revealed that higher PLR 24 h after rtPA was independently associated with increased risks of poor outcome and death. However, the PLR on admission was not associated with the risks of poor outcome and death. The individualized prediction model for poor outcome based on the 24-h PLR exhibited favorable discrimination (areas under the curves of the training and validation groups: 0.743 and 0.729, respectively), calibration (P > 0.05), and clinical usefulness. Conclusions: We found the PLR to be a variable that potentially predicts the risks of poor outcome and death in patients with acute ischemic stroke 24 h after rtPA; however, it cannot make the same prediction on admission.